Lung Neutrophilic Recruitment and IL-8/IL-17A Tissue Expression in COVID-19 - Azevedo, Marina Luise Viola; Zanchettin, Aline Cristina; Vaz de Paula, Caroline Busatta; Motta Júnior, Jarbas da Silva; Malaquias, Mineia Alessandra Scaranello; Raboni, Sonia Mara; Neto, Plínio Cezar; Zeni, Rafaela Chiuco; Prokopenko, Amanda; Borges, Nícolas Henrique; Godoy, Thiago Mateus; Benevides, Ana Paula Kubaski; et al. (Frontiers in Immunology, 2021)
The new SARS-CoV-2 virus differs from the pandemic Influenza A virus H1N1 subtype (H1N1pmd09) how it induces a pro-inflammatory response in infected patients. This study aims to evaluate the involvement of SNPs and tissue expression of IL-17A and the neutrophils recruitment in post-mortem lung samples from patients who died of severe forms of COVID-19 comparing to those who died by H1N1pdm09. Twenty lung samples from patients SARS-CoV-2 infected (COVID-19 group) and 10 lung samples from adults who died from a severe respiratory H1N1pdm09 infection (H1N1 group) were tested. The tissue expression of IL-8/IL-17A was identified by immunohistochemistry, and hematoxylin and eosin (H&E) stain slides were used for neutrophil scoring. DNA was extracted from paraffin blocks, and genotyping was done in real time-PCR for two IL17A target polymorphisms. Tissue expression increasing of IL-8/IL-17A and a higher number of neutrophils were identified in samples from the H1N1 group compared to the COVID-19 group. The distribution of genotype frequencies in the IL17A gene was not statistically significant between groups. However, the G allele (GG and GA) of rs3819025 was correlated with higher tissue expression of IL-17A in the COVID-19 group. SARS-CoV-2 virus evokes an exacerbated response of the host’s immune system but differs from that observed in the H1N1pdm09 infection since the IL-8/IL-17A tissue expression, and lung neutrophilic recruitment may be decreased. In SNP rs3819025 (G/A), the G allele may be considered a risk allele in the patients who died for COVID-19.